2005
DOI: 10.1111/j.1365-2141.2004.05357.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet size deviation width, platelet large cell ratio, and mean platelet volume have sufficient sensitivity and specificity in the diagnosis of immune thrombocytopenia

Abstract: SummaryWe investigated the significance of the platelet indices, mean platelet volume (MPV), platelet size deviation width (PDW), and platelet‐large cell ratio (P‐LCR), in the diagnosis of thrombocytopenia by comparing these levels in 40 patients with hypo‐productive thrombocytopenia (aplastic anaemia; AA) and 39 patients with hyper‐destructive thrombocytopenia (immune thrombo‐cytopenia; ITP). The sensitivity and specificity of platelet indices to make a diagnosis of ITP were also compared. All platelet indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
206
1
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(234 citation statements)
references
References 16 publications
21
206
1
6
Order By: Relevance
“…Four patients (2 male Signifi cance : * p < 0.05; ** p < 0.01 Relation of blood platelet count during carbamazepine and oxcarbazepine treatment with daily dose, and serum concentrations of carbamazepine, carbamazepine-10,11-epoxide, and 10-hydroxycarbazepine and 2 female) with a mean age of 60.5 ± 11.5 years (range 30-83 years) treated with CBZ and a female of 27 years treated with OXCBZ had thrombocytopenia, with a platelet count of 125 ± 6.29 x 10 9 /l (range 112-148 x 10 9 /l), VPM of 9.72 ± 0.47 fl (range 8.1-11.0 fl) and PDW of 61.08 ± 7.06 % (range 44.9-83.8 %). In accordance with previously published data on the possible discrimination of hypo-productive or hyper-destructive thrombocytopenia using these platelet indices 12,13 , in the 5 epileptic patients with decreased platelet count, this fact may be due to a hyper-destruction of peripheral blood platelets. Furthermore, the calculation of the residual PDW according to Osselaer et al 14 in the 8 patients with a platelet count greater than 400 x 10 9 /l, suggests that in at least 7 of the cases, discrete thombocytosis (466 ± 27 x 10 9 /l) was secondary or reactive.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Four patients (2 male Signifi cance : * p < 0.05; ** p < 0.01 Relation of blood platelet count during carbamazepine and oxcarbazepine treatment with daily dose, and serum concentrations of carbamazepine, carbamazepine-10,11-epoxide, and 10-hydroxycarbazepine and 2 female) with a mean age of 60.5 ± 11.5 years (range 30-83 years) treated with CBZ and a female of 27 years treated with OXCBZ had thrombocytopenia, with a platelet count of 125 ± 6.29 x 10 9 /l (range 112-148 x 10 9 /l), VPM of 9.72 ± 0.47 fl (range 8.1-11.0 fl) and PDW of 61.08 ± 7.06 % (range 44.9-83.8 %). In accordance with previously published data on the possible discrimination of hypo-productive or hyper-destructive thrombocytopenia using these platelet indices 12,13 , in the 5 epileptic patients with decreased platelet count, this fact may be due to a hyper-destruction of peripheral blood platelets. Furthermore, the calculation of the residual PDW according to Osselaer et al 14 in the 8 patients with a platelet count greater than 400 x 10 9 /l, suggests that in at least 7 of the cases, discrete thombocytosis (466 ± 27 x 10 9 /l) was secondary or reactive.…”
Section: Resultssupporting
confidence: 75%
“…For the total number of patients studied, in 184 cases (93 %) the number of platelets was within the reference range (150-400 x 10 9 /l), with mean values for the platelet count (255.21 ± 4.52 x 10 9 /l), VPM (7.95 ± 0.07 fl) and PDW (49.52 ± 0.55 %) similar to those found in control subjects 20 . In the 5 patients we found with thrombocytopenia (4 treated with CBZ and 1 with OXCBZ), the results obtained for the platelet indices VPM and RDW 12,13 suggest a hyper-destruction and reduced blood platelet survival similar to that seen in immune thrombocytopenia. Although the patients treated with OXCBZ shown a lower prevalence for thrombocytopenia (1.7 %) than those treated with CBZ (2.9 %), the confi rmation of this subject in a greater number of patients appears mandatory.…”
Section: Discussionmentioning
confidence: 62%
“…MPV and platelet distribution width (PDW) are the platelet indices measured by automatic cell analyser and this may be helpful to distinguish hypoproductive thrombocytopenia (aplastic anemia) and hyperproductive thrombocytopenia (idiopathic thrombocytopenic purpura) and for the differential diagnosis of thrombocytosis [2][3][4], as well as to predict the prognosis of coronary artery disease. Recently, Yazici et al reported that MPV reflects the disease activity of rheumatoid arthritis [5].…”
Section: To the Editormentioning
confidence: 99%
“…In AA mean platelet large cell ratio was 21.07(±5.51) % and in ITP mean platelet large cell ratio was 36.68(±7.91) % and was statistically significant. Kaito et al [11] study reported that, the platelet count was similar in both groups. All platelet indices were significantly higher in ITP than in AA (p<0.001).…”
Section: Discussionmentioning
confidence: 98%
“…P-LCR cut of value >40 sensitivity was 100% and specificity was 63.0%. Kaito et al [11] study the sensitivity and specificity of platelet indices to make a diagnosis of ITP was calculated under various cut-off ranges. The referential ranges at their institute were 8.4-12 fL for MPV, 8-14 fL for PDW and 10-30% for P-LCR.…”
Section: Discussionmentioning
confidence: 99%